Personal and Contextual Factors Influencing Teacher Agency in Overcoming Students’ Learning Difficulties - Yuni Budi Lestari; Kamaludin Yusra; Nurachman Hanafi; Nawawi Nawawi; Nuriadi Nuriadi (Makassar State University, 2022)
Abstract: Research demonstrates that the extent to which teacher agency is achieved is influenced by personal and contextual conditions of possibility and constraints. This study identifies personal and contextual factors that influence teacher agency in overcoming student learning difficulties. Although there are many studies showing factors influencing teacher agency in various contexts, little research, if any, has been done on personal and contextual factors influencing teacher agency in overcoming students’ learning difficulties in the Indonesian higher education. This research filled the gap by examining the factors influencing teacher agency in overcoming student learning difficulties at a postgraduate English department at a government university in West Nusa Tenggara, Indonesia. This research is a case study involving four (4) university teachers who teach at the department as the research participants who were selected purposively. Data of the study were collected through in-depth interviews. Semi-structured interview was employed in which open and close-ended questions about personal and contextual factors influencing teacher agency in helping students with learning difficulties were given. The data form the interviews were analysed using qualitative content analysis. Results demonstrated that a number of personal and contextual factors enabled and constrained teacher agency enactment when overcoming student difficulties in learning. Personal factors include sound pedagogical knowledge and teaching experience. Contextual factors involve having collaborative relationships among university teachers and students, and school management. As teachers work under varying constraints even within the same institution, further research needs to be conducted to uncover more factors influencing teacher agency. Keywords: Personal Factor, Contextual Factor, Teacher Agency, Students’ Learning Difficulty